Decorate Your Home With Colour A Practical And Inspirational Guide With Step-By-Step Projects - Libby Norman
Color lies at the heart of all successful decorating schemes$1 (Bbut with so many shades and combinations available, how can you narrow the options and decide what's right? Just open this inspirational and gloriously illustrated sourcebook! Starting with first principles, it describes how to come up with a plan; suggests tried and trusted blending techniques; and reveals designer tricks for layering hues, creating depth and interest, and preparing surfaces for a smooth and professional finish. The following chapters each deal with a specific color, and include relevant projects such as painting a floor, designing a feature wall, adding effects, and stamping and stenciling.s